The effect of herbal extract Foeniculum vulgare Mill. solution on the mechanical and wetting properties of heat polymerized denture base resin - Petrović Milica B.; Kitić Dušanka; Samardžić Nataša; Kostić Milica; Stojanović Goran; Igić Marko; Kostić Milena; Mionić-Ebersold Marijana (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Introduction. Commercially used chemical dental cleansers adversely affect mechanical properties of denture. Therefore, there is a need for finding an alternative which will not change the surface properties of material. Aim. This paper studied the effect of the herbal extract (Foeniculum vulgare Mill.) solution on the wetting and mechanical properties of heat-polymerized denture base resin compared to the same properties of the same resin in the native state (in air) and exposed only to aqueous environment. Material and methods. Rectangular shape of heat polymerized acrylic resin (15 mm x 15 mm x 3 mm) were prepared and divided into: (i) sample continuously exposed to air - AIR; (ii) sample continuously exposed to distilled water - DW; and (iii) sample exposed to 10% solution of the fennel leaves extract - PES. Wetting properties were measured by sessile drop method, whereas mechanical properties were analyzed by nanoindentation method. Results. Results showed that samples AIR had the lowest ΘC value 64.5±2.3 °, while the other two samples DW and PES had similar ΘC values (75.4±3.3 °, 75.7±4.7 °, respectively). Furthermore, there was no statistically significant difference in hardness coefficient, while Young's modulus showed a significant difference (p < 0.005) only between the samples AIR and DW. Conclusion. The obtained values confirmed that fennel extract can be used as successful and efficient cleanser, without degradation of denture surface.